The power circuits, the duality of controls and performance appraisal: evidence from a Sri Lankan private university - S. M. Chaturika Seneviratne; Ashan Martino (International Journal of Financial, Accounting, and Management, 2021)
Purpose: The study investigates the impacts stemming from the interplay between episodic, dispositional and systemic power circuits through which organisational agents influence or transform the coercive and enabling aspects ingrained in the performance appraisal process in a university setting. Research methodology: The paper uses a single case study method based on a private university. Data was collected using interviews, documentary evidence and observations. Results: We found that coercive controls become dominance over enabling controls of performance appraisal as an outcome of the ongoing implicit struggle between internal agents who pursue diverse interests and power relations in the private university setting. Limitations: As the research is directed towards the selection of in-depth inquiry of specific setting infused with culture, values, and ideology, it might cause to diminish the researcher’s analytical objectivity and independence of the research. Contribution: The study suggests that the realizing of power remained with the agent’s discretion within day-to-day interrelations. Therefore, the agents’ power relations are significant in deciding the intensity of dual controls in the performance appraisal practice. Keywords: Performance appraisal, Power circuits, Enabling controls, Coercive controls, University